2019
DOI: 10.1177/0891988719866926
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health and Life Satisfaction of Elderly People: Testing the Moderating Effects of Social Support, Attitudes Toward Aging, and Senior Privilege

Abstract: As health declines with age, it is critical to explore moderators that could buffer the impact of declining health on life satisfaction of elderly people. This study aims to test the moderating effects of social support, attitudes toward aging, and senior privilege on the relationship between perceived health and life satisfaction among elderly people. The study used a sample of 5809 Chinese elderly people. Multiple regression analyses were performed to test the moderating effects of the study variables along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…In addition, better self‐reported physical and mental health, higher levels of satisfaction, better financial status and lower levels of anxiety and depression have been associated with positive attitude towards ageing (Bryant et al., 2012). Attitude towards ageing as an intrapersonal mind‐set directly influences the life satisfaction of elderly people (Liu et al., 2019), and higher levels of life satisfaction is associated with increased quality of life (Stenhagen, Ekström, Nordell, & Elmståhl, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, better self‐reported physical and mental health, higher levels of satisfaction, better financial status and lower levels of anxiety and depression have been associated with positive attitude towards ageing (Bryant et al., 2012). Attitude towards ageing as an intrapersonal mind‐set directly influences the life satisfaction of elderly people (Liu et al., 2019), and higher levels of life satisfaction is associated with increased quality of life (Stenhagen, Ekström, Nordell, & Elmståhl, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals’ attitude towards ageing has a significant impact on health behaviours and outcomes (Bryant et al., 2016). A positive attitude towards ageing is associated with better self‐reported physical health and well‐being, lower levels of depression and anxiety, and increased life satisfaction (Bryant et al., 2012; Lamont, Nelis, Quin, & Clare, 2017; Liu, Wei, Peng, & Xue, 2019). Moreover, a positive attitude towards own ageing among older adults serves as a psychological resource to moderate the effects of the ageing process (Mock & Eibach, 2011) and associated with better physical health and functioning, mental health and higher level of self‐efficacy (Bellingtier & Neupert, 2018; Tovel, Carmel, & Raveis, 2019), better sense of dignity (Kisvetrova et al, 2019) and protective factor for health including those with cancer (Martin et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that social support from the immediate circle may become increasingly less common due to modern lifestyles (divorce, geographic mobility). Beyond the field of marketing (Van Dolen and Weinberg, 2017; Beatson et al , 2020), social support has been examined in many disciplines, namely, psychology, social psychology, health education and medicine (Benkel et al , 2009; Calvete and de Arroyabe, 2012; Lin et al , 2020; Liu et al , 2020). These studies have rapidly attempted to distinguish various types of social support differentiated either by their nature and the function performed or by the fact that the social support is perceived, objective or used (Liu et al , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Beyond the field of marketing (Van Dolen and Weinberg, 2017; Beatson et al , 2020), social support has been examined in many disciplines, namely, psychology, social psychology, health education and medicine (Benkel et al , 2009; Calvete and de Arroyabe, 2012; Lin et al , 2020; Liu et al , 2020). These studies have rapidly attempted to distinguish various types of social support differentiated either by their nature and the function performed or by the fact that the social support is perceived, objective or used (Liu et al , 2020). One of the most common classifications (Van Dolen and Weinberg, 2017) distinguishes five types of social support (informational, tangible, esteem, network and emotional).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation